The Effect of E-recruitment on Interest in Applying for Jobs with Company Reputation as a Mediation Variable - Muhamad Ekhsan; Ernasari (Journal of Research in Business, Economics, and Education, 2022)
Companies compete for customers and gain a competitive advantage. In addition, they also compete to win candidates who are competent and capable in their fields. The current workforce is shifting to the millennial generation. According to a survey of internet usage by age by the Association of Indonesian Internet Service Providers (APJII), the millennial generation made the largest contribution at 64%. This shows that the millennial generation has a large internet consumption pattern, and internet user data information is increasing from year to year. However, utilization to find work is still low. This study aims to determine the effect of E-recruitment on the desire to apply for a job, the effect of company reputation on the desire to apply for a job and the effect of e-recruitment on asking to apply for a job mediated by company reputation. Data was collected by distributing questionnaires via google form with random sampling technique. Questionnaires were distributed to some students of the 2017 Faculty of Economics and Business with a total of 97 respondents. Analysis The data is processed using SmartPLS. The results show that E-Recruitment has no effect on interest in applying for work, E-recruitment affects company reputation, Company reputation affects interest in applying for work, Company reputation is able to mediate E-recruitment on interest in applying for work.